Uterine Tumors Resembling Ovarian Sex Cord Tumors: Case Report of Rare Pathological and Clinical Entity - Rotem Sadeh; Yakir Segev; Meirav Schmidt; Jacob Schendler; Tamar Baruch; Ofer Lavie (Hindawi Limited, 2017)
Uterine tumors resembling ovarian sex cord tumors (UTROSCT) are rare uterine neoplasms. These tumors are usually benign, displaying a nodular or polypoid growth pattern; common occurrence is observed at the 4th to 6th decade of life. This entity is divided according to clinical behavior and pathological typical findings including different immunohistochemical staining. Traditionally type I tumors show a predominant endometrial stromal pattern with less than 50% ovarian sex cord component. This type has been shown to behave more aggressively with a decreased disease free survival period. Type II tumors, the classical UTROSCT, are less invasive but have the tendency to recur. We report a case of a 57-year-old patient presenting with postmenopausal bleeding. Hysteroscopic polypectomy showed the diagnosis of UTROSCT. This case presents a less morbid minimally invasive treatment plan and exemplifies that in patients where low malignant potential exists and their will is taken into consideration such management is both crucial and correct.